American Foreign Policy Under President Donald Trump: Continuities, Changes and Implications for East Asian Stability - Bunyavejchewin, Poowin; Chotisut, Kridsana (Thai Journal of East Asian Studies, 2019)
Many observers expected radical changes and discontinuities in the US foreign policy under President Donald Trump who won the presidential elections in 2016. The first year of the Trump administration, however, suggested that the conduct of foreign policy in general, especially on issues where stakes were considerably high, continued the path the previous administration chose and followed the American tradition in foreign affairs, despite the fact that some issues closely related to Trump’s election campaigns were changed in accordance to the promises he made to his political supporters.